2023
DOI: 10.14569/ijacsa.2023.0140310
|View full text |Cite
|
Sign up to set email alerts
|

Self-Adapting Security Monitoring in Eucalyptus Cloud Environment

Abstract: This paper discusses the importance of virtual machine (VM) scheduling strategies in cloud computing environments for handling the increasing number of tasks due to virtualization and cloud computing technology adoption. The paper evaluates legacy methods and specific VM scheduling algorithms for the Eucalyptus cloud environment and compare existing algorithms using QoS. The paper also presents a selfadapting security monitoring system for cloud infrastructure that takes into account the specific monitoring re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is characterized by a global cloud infrastructure, implying that the services offered within this framework have a wide-ranging geographical reach. Tenants within this environment have the authority to govern their VMs, affording them control over a networked ecosystem that is integral to their operations and functionalities [25][26][27]. The mechanism used for this study in the Eucalyptus Cloud Environment is shown in Figure 1 [25][26][27].…”
Section: Iaas Cloud Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by a global cloud infrastructure, implying that the services offered within this framework have a wide-ranging geographical reach. Tenants within this environment have the authority to govern their VMs, affording them control over a networked ecosystem that is integral to their operations and functionalities [25][26][27]. The mechanism used for this study in the Eucalyptus Cloud Environment is shown in Figure 1 [25][26][27].…”
Section: Iaas Cloud Environmentmentioning
confidence: 99%
“…Tenants within this environment have the authority to govern their VMs, affording them control over a networked ecosystem that is integral to their operations and functionalities [25][26][27]. The mechanism used for this study in the Eucalyptus Cloud Environment is shown in Figure 1 [25][26][27]. Design Principles…”
Section: Iaas Cloud Environmentmentioning
confidence: 99%